The neurocognitive consequences of the wandering mind: a mechanistic account of sensory-motor decoupling - Kam, Julia W.; Handy, Todd C. (Frontiers in Psychology, 2013)
A unique human characteristic is our ability to mind wander – a state in which we are free to engage in thoughts that are not directly tied to sensations and perceptions from our immediate physical environment. From a neurocognitive perspective, it has been proposed that during mind wandering, our executive resources are decoupled from the external environment and directed to these internal thoughts. In this review, we examine an underappreciated aspect of this phenomenon – attenuation of sensory-motor processing – from two perspectives. First, we describe the range of widespread sensory, cognitive and motor processes attenuated during mind wandering states, and how this impacts our neurocognitive processing of external events. We then consider sensory-motor attenuation in a class of clinical neurocognitive disorders that have ties to pathological patterns of decoupling, reviews suggesting that mind wandering and these clinical states may share a common mechanism of sensory-motor attenuation. Taken together, these observations suggest the sensory-motor consequences of decoupled thinking are integral to normal and pathological neurocognitive states.